A variant of multifocal motor neuropathy with acute, generalised presentation and persistent conduction blocks. Issue 11 (14th November 2003) - Lefaucheur, J-P; Gregson, N A; Gray, I; von Raison, F; Bertocchi, M; Créange, A
Abstract : Objective: Multifocal motor neuropathy with persistent conduction blocks is classically described as a chronic neuropathy with progressive onset, and acute forms have not previously been characterised. We report four cases of severe motor impairment with acute and generalised onset and with persistent motor conduction blocks. Patients and results: An acute tetraparesis with diffuse areflexia but little or no sensory disturbance was the clinical picture. Serial electrophysiological tests showed persistent multifocal motor conduction blocks with absent F waves in most tested motor nerves. No or minor abnormalities of the sensory nerve action potentials were observed. Cerebrospinal fluid contained normal or mildly increased protein levels (<1 g/l) without cells. Campylobacter jejuni serology was negative in three patients and consistent with past infection in one patient. Anti-ganglioside antibodies were positive in three patients. A five day course of intravenous immunoglobulins produced nearly complete symptom resolution in three patients and was ineffective in one patient. Conclusion: Because of the persistence of multifocal motor conduction blocks for several weeks or months as the isolated electrophysiological feature, these cases could not be consistent with Guillain–Barré syndrome or chronic inflammatory demyelinating polyneuropathy. They suggest an original variant of multifocal motor neuropathy with an acute and generalised initial presentation and persistent motor conduction blocks affecting all four limbs.